Enhanced Symbiotic Characteristics in Bacterial Genomes with the Disruption of rRNA Operon - Hyeonju Ahn (Biology, 2020)
Ribosomal RNA is an indispensable molecule in living organisms that plays an essential role in protein synthesis. Especially in bacteria, 16S, 23S, and 5S rRNAs are usually co-transcribed as operons. Despite the positive effects of rRNA co-transcription on growth and reproduction rate, a recent study revealed that bacteria with unlinked rRNA operons are more widespread than expected. However, it is still unclear why the rRNA operon is broken. Here, we explored rRNA operon linkage status in 15,898 bacterial genomes and investigated whether they have common features or lifestyles; 574 genomes were found to have unlinked rRNA operons and tended to be phylogenetically conserved. Most of them were symbionts and showed enhanced symbiotic genomic features such as reduced genome size and high adenine–thymine (AT) content. In an eggNOG-mapper analysis, they were also found to have significantly fewer genes than rRNA operon-linked bacteria in the “transcription” and “energy production and conversion in metabolism” categories. These genomes also tend to decrease RNases related to the synthesis of ribosomes and tRNA processing. Based on these results, the disruption of the rRNA operon seems to be one of the tendencies associated with the characteristics of bacteria requiring a low dynamic range.